Humic substance fractions and attributes of histosols and related high-organic-matter soils form Brazil. - VALLADARES, G. S. (2007)
Knowledge of the distribution of soil organic matter (SOM) fractions is important in managing soils toward a sustainable agricultural system ina tropical environment, However, data on Histosols in limited. This study developed 19 regions of Brazil. Soil organic matter was fractionated into fulvic acids (FAF), humic acids (HAF), and humin (HUM). The ratios haf/faf and ae (alkaline extract)/HUM were calculated. The objectives were to evaluete the method for SOM fractionating in Histosols and related soils and to correlate the distribution of organic fractions with other soil attributes. The humic fractions presente significant.